Juventude: estudos em representações sociais - Leite, Angela Helena Rodrigues (2014)
Studies about the young have focused on themes such as violence, sexuality, drugs and criminality, assuming that these are the interests of youth or at least are part of their major concerns. Will be? Certainly these subjects are issues of concern and interest of human sciences researchers. However, we must to understand this young from themes present in your own speeches, not from previously established objects which could conditioned a view of what it important or should be important them. This approach enables to be closer of this subject, knowing the dynamic which define their life in a broader social context. Thus, the aim of this research is to analyses the social representation which the young are building about the youth, from topics that are interesting to them and their positions on these topics. The Social Representation Theory based this research and enable to access aspects of the subjectivity that are been building from these young in a specific social context. As methodological approach, we did an investigation through a Focal Group. In a public school in Osasco, São Paulo, it was created a Group with thirteen subjects from the 2º and 3º year of High School. This procedure allowed the knowledge of the experiences anchored in their daily lives, the understanding of the processes of construction of realities, the sharing ideas and different perspectives on the same issue, as well as the ways they collectively prepare their representations. The interview was transcript and submitted to ALCESTE software, which classified the subject s speeches in three classes divided into: The School , Self and the Others and The Politics . Starting from the qualitative analyses of the categories, the results essentially demonstrated that the young cannot understand himself as an autonomous or protagonist of the situations: as regards to the school, their discourses are based on complains about the poor quality of education, delegating mainly to the teacher as well as to the other actors of the institution, the main role of the process conduction; as regards the social relations, the young seems to understand themselves as subordinate to standards imposed, without autonomy to quarrel or establish criteria for their own choices choices which are, in turn, specially conditioned to institutions such as Church and Family; Ultimately, as regards to politic, the analyses suggest a great detachment from the young with the theme. They set forth to be guided by media discourses and showed no efforts to criticize or even sustain these speeches with theoretical justifications